Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sand dredging is associated with benthic habitat alteration and chronic turbidity with profound ecological consequences likely for the UK and Ireland's largest freshwater lake - Neil Reid; Rachel Stewart; Marc Ruddock; Gerard Hamill; Christopher Hackney (Journal of Environmental Management, 2026)

Restoration of exploited lowland raised bogs recovered plant and invertebrate taxa richness and peatland specialists within a decade - Juliet Everson; Ann McCann; Pat Walls; Neil Reid (Journal of Environmental Management, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Apparent flush-foraging in a crested guan (Penelope purpurascens) family party - Kathryn E. Vance; Duncan A. J. Pandya; Samuel E. I. Jones; Neil Reid; Hannah M. J. Hoskins; Thomas E. Martin (Ornithology Research, 2026)

Evolving food and beverage landscapes: A multidisciplinary inquiry into technological innovation, policy, and industry structure - Haoying Wang; Rafael Garduno-Rivera; Neil Reid (Applied Geography, 2025)

Beyond maximum density: multi-parameter insights into Scots pine climate sensitivity - Inga K. Homfeld; Frederick Reinig; Edurne Martinez del Castillo; Max C. A. Torbenson; Oliver Konter; Rob Wilson; Paul J. Krusic; Neil J. Loader; Hakan Grudd; Emily Reid; Kayleigh Letherbarrow; Jan Esper (Trees, 2025)
Key message Climate sensitivity of Pinus sylvestris has changed in minimum density while maximum density remains mostly stable, suggesting the use of additional density parameters could help detect response changes. Abstract As one of Eurasia's most widely distributed conifer species, Pinus sylvestris L. is frequently used in dendroclimatological reconstructions based on tree-ring width (TRW) and maximum latewood density (MXD). However, the climatic signals of additional parameters such as earlywood/latewood density (EWD/LWD) or minimum density (MND) are often overlooked, leaving their skill unexplored. Here, we investigate the growth responses of multiple P. sylvestris tree-ring parameters to ongoing climate change at two sites with contrasting climatic conditions using well-replicated density data from Scotland and Sweden. Correlations with mean, minimum, and maximum temperatures are strongest for LWD and MXD at both sites, with coefficients ranging from 0.5 to 0.7 for July, August, and the June–August season ( p < 0.05). A significant ( p < 0.05) negative correlation between MND and July temperatures was identified in the Swedish Torneträsk (TOR) data ( p < 0.05), which diminished since the late twentieth century. A comparable inverse MND temperature signal and change into the twenty-first century is not reflected in northern Scotland’s overall wetter and warmer site, suggesting a fundamental physiological change in tree-ring formation under global warming. A shift in the sensitivity of tree growth at northern European sites could reduce the effectiveness of proxies from such locations, posing implications for high-resolution climate reconstructions.

The economic geography of beer production in the context of trade liberalization and economic nationalism: The Mexican experience - Haoying Wang; Rafael Garduno-Rivera; Neil Reid (Applied Geography, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Invasion of farmland hedgerows by non-native small mammals is associated with lower soil surface invertebrate diversity, abundance, body size and biomass - W. Ian Montgomery; Sally S. J. Montgomery; James O’Neill; Neil Reid (Biological Invasions, 2024)
Small mammals in farmland hedgerows feed on soil surface invertebrates with non-native invasive species potentially affecting prey species and populations. We investigated terrestrial invertebrates using pitfall traps and leaf litter samples across four zones of invasion in Ireland: (1) native species only (wood mouse Apodemus sylvaticus and pygmy shrew Sorex minutus ), (2) natives plus the non-native bank vole ( Myodes glareolus ), (3) natives plus the non-native greater white-toothed shrew ( Crocidura russula ) and (4) natives plus both. After accounting for regional and local environmental variation, small mammal invasion was associated with lower invertebrate species richness (9–39% lower than uninvaded zones), reduced abundance (18–56% lower), shorter arthropod body length (24–52% shorter) and lower arthropod biomass (63–89% lower). Negative effects were observed on a wide range of disparate functional groups spanning phytophagous, detritivorus, zoophagous and omnivorous taxa including: the Staphylinidae, Carabidae and Coleoptera larvae, Isopoda, Diplopoda, Diptera, Hymenoptera, Pulmonata and Acari. The greater white-toothed shrew had greater negative effects than the bank vole with presence of both having greater effects than either alone though the majority of their combined effects were largely attributable to the former. The bank vole may mitigate some of the negative effects of the greater white-toothed shrew on invertebrate abundance perhaps indicating of some form of trophic interaction. Predation of detritivores and large invertebrate predators may impact farmland ecosystem service delivery i.e. nutrient cycling and pest biocontrol. Hedgerow biodiversity loss may induce indirect trophic cascades negatively impacting other taxa including farmland birds.

Landscape genetics identifies barriers to Natterjack toad metapopulation dispersal - Marina I. Reyne; Kara Dicks; Jason Flanagan; Paul Nolan; Joshua P. Twining; Aurélie Aubry; Mark Emmerson; Ferdia Marnell; Sarah Helyar; Neil Reid (Conservation Genetics, 2023)
Habitat fragmentation and loss reduce population size and connectivity, which imperils populations. Functional connectivity is key for species persistence in human-modified landscapes. To inform species conservation management, we investigated spatial genetic structure, gene flow and inferred dispersal between twelve breeding sites of the Natterjack toad ( Bufo calamita ); regionally Red-Listed as Endangered in Ireland. Spatial genetic structure was determined using both Bayesian and non-Bayesian clustering analysis of 13 polymorphic microsatellite loci genotyping 247 individuals. We tested the influence of geographic distance, climate, habitat, geographical features, and anthropogenic pressure on pairwise genetic distances between breeding sites using Isolation-by-distance and Isolation-by-resistance based on least-cost path and circuit theory models of functional connectivity. There was clear spatial structuring with genetic distances increasing with geographic distance. Gene flow was best explained by Isolation-by-resistance models with coniferous forestry plantations, bog, marsh, moor and heath, scrub, anthropogenic presence (Human Influence Index) and rivers (riparian density) identified as habitats with high resistance to gene flow while metapopulation connectivity was enhanced by coastal habitats (beaches, sand dunes and salt marshes) and coastal grassland. Despite substantial declines in census numbers over the past 15 years and its regional status as Endangered, the Natterjack toad population in Ireland retains high genetic diversity. If declines continue, maintaining habitat connectivity to prevent genetic erosion by management of coastal grasslands, pond construction and assisted migration through translocation will be increasingly important.

Bidirectional hybridisation and introgression between introduced European brown hare, Lepus europaeus and the endemic Irish hare, L. timidus hibernicus - Neil Reid; Maria F. Hughes; Rosaleen A. Hynes; W. Ian Montgomery; Paulo A. Prodöhl (Conservation Genetics, 2022)
Introduced non-native species can threaten native species through interspecific hybridisation and genetic introgression. We assessed the prevalence of hybridisation and introgression between introduced European brown hare, Lepus europaeus , and the endemic Irish hare, L. timidus hibernicus . Roadkill hares ( n = 56) were sequenced for a 379bp section of the mitochondrial DNA D-loop and a 474bp segment of the nuclear transferrin ( Tf ) gene. A species-specific indel in the transferrin gene was present in L.t. hibernicus and absent in L. europaeus . Excluding three hares from which molecular data could not be recovered, 28 hares (53%) were native L.t. hibernicus , 7 (13%) were non-native L. europaeus and 18 (34%) were hybrids; of which 5 (28%) were first generation (F1) involving bidirectional crosses with mismatched nuclear and mtDNA (3 ♂ europaeus x ♀ hibernicus and 2 ♂ hibernicus x ♀ europaeus ). Mixed nuclear transferrin sequences suggested 13 (72%) of hybrids were at least 2nd generation (F2) with 9 (69%) possessing L.t. hibernicus and 4 (31%) L. europaeus mtDNA (the latter indicative of hybrid backcrossing with the non-native). The prevalence of hybridisation at similar mountain-brown hare contact zones throughout Europe is notably lower (4–16%) and typically unidirectional (♂ europaeus x ♀ timidus ). A high prevalence of bidirectional hybridisation and introgression (in association with projected climate change) may favour the introduced species over the native. Genetic surveillance and population monitoring are needed to further explore the potential conservation implications of European brown hare in Ireland.

Population genetic structure of the Natterjack toad (Epidalea calamita) in Ireland: implications for conservation management - Marina Reyne; Kara Dicks; Claire McFarlane; Aurélie Aubry; Mark Emmerson; Ferdia Marnell; Neil Reid; Sarah Helyar (Conservation Genetics, 2022)
Molecular methods can play a crucial role in species management and conservation. Despite the usefulness of genetic approaches, they are often not explicitly included as part of species recovery plans and conservation practises. The Natterjack toad ( Epidalea calamita ) is regionally Red-Listed as Endangered in Ireland. The species is declining and is now present at just seven sites within a highly restricted range. This study used 13 highly polymorphic microsatellite markers to analyse the population genetic diversity and structure. Genetic diversity was high with expected heterozygosity between 0.55 and 0.61 and allelic richness between 4.77 and 5.92. Effective population sizes were small ( N e < 100 individuals), but not abnormal for pond breeding amphibians. However, there was no evidence of historical or contemporary genetic bottlenecks or high levels of inbreeding. We identified a positive relationship between N e and breeding pond surface area, suggesting that environmental factors are a key determinant of population size. Significant genetic structuring was detected throughout the species’ range, and we identified four genetic entities that should be considered in the species’ conservation strategies. Management should focus on preventing further population declines and future loss of genetic diversity overall and within genetic entities while maintaining adequate local effective population size through site-specific protection, human-mediated translocations and head-start programs. The apparent high levels of genetic variation give hope for the conservation of Ireland’s rarest amphibian if appropriately protected and managed.

The evolutionary pathways for local adaptation in mountain hares - Iwona Giska; João Pimenta; Liliana Farelo; Pierre Boursot; Klaus Hackländer; Hannes Jenny; Neil Reid; W. Ian Montgomery; Paulo A. Prodöhl; Paulo C. Alves; José Melo‐Ferreira (Molecular Ecology, 2022)
Understanding the evolution of local adaptations is a central aim of evolutionary biology and key for the identification of unique populations and lineages of conservation relevance. By combining RAD sequencing and whole‐genome sequencing, we identify genetic signatures of local adaptation in mountain hares ( Lepus timidus ) from isolated and distinctive habitats of its wide distribution: Ireland, the Alps and Fennoscandia. Demographic modelling suggested that the split of these mountain hares occurred around 20 thousand years ago, providing the opportunity to study adaptive evolution over a short timescale. Using genome‐wide scans, we identified signatures of extreme differentiation among hares from distinct geographic areas that overlap with area‐specific selective sweeps, suggesting targets for local adaptation. Several identified candidate genes are associated with traits related to the uniqueness of the different environments inhabited by the three groups of mountain hares, including coat colour, ability to live at high altitudes and variation in body size. In Irish mountain hares, a variant of ASIP , a gene previously implicated in introgression‐driven winter coat colour variation in mountain and snowshoe hares ( L . americanus ), may underlie brown winter coats, reinforcing the repeated nature of evolution at ASIP moulding adaptive seasonal colouration. Comparative genomic analyses across several hare species suggested that mountain hares’ adaptive variants appear predominantly species‐specific. However, using coalescent simulations, we also show instances where the candidate adaptive variants have been introduced via introgressive hybridization. Our study shows that standing adaptive variation, including that introgressed from other species, was a crucial component of the post‐glacial dynamics of species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Development and validation of a quantitative qPCR assay for detecting Natterjack toad (Epidalea calamita) eDNA samples - Marina Reyne; Amanda M. Naaum; Ferdia Marnell; Neil Reid; Sarah J. Helyar (Conservation Genetics Resources, 2021)
The Natterjack toad ( Epidalea calamita ) is the rarest amphibian species in Ireland, regionally Red-Listed as Endangered. We applied an eDNA approach to detect species presence in breeding pond water samples. We developed a species-specific qPCR assay targeting the cytochrome c oxidase subunit I (COI). The assay was tested in silico, in vitro (DNA extracted from tissue) and in vivo (DNA extracted from water samples). Water samples were collected from five ponds with known Natterjack toad presence or absence to validate the sensitivity and specificity of the assay. The assay was shown to be highly specific to the Natterjack toad and tested positive only against toad tissue samples and eDNA samples from ponds with known species presence. We believe this method can be used for rapid assessment of species occurrence.

Regime shift tipping point in hare population collapse associated with climatic and agricultural change during the very early 20th century - Neil Reid; Jon E. Brommer; Nils C. Stenseth; Ferdia Marnell; Robbie A. McDonald; W. Ian Montgomery (Global Change Biology, 2021)
Animal populations at northern latitudes may have cyclical dynamics that are degraded by climate change leading to trophic cascade. Hare populations at more southerly latitudes are characterized by dramatic declines in abundance associated with agricultural intensification. We focus on the impact of historical climatic and agricultural change on a mid‐latitude population of mountain hares, Lepus timidus hibernicus . Using game bag records from multiple sites throughout Ireland, the hare population index exhibited a distinct regime shift. Contrary to expectations, there was a dynamical structure typical of northern latitude hare populations from 1853 to 1908, during which numbers were stable but cyclic with a periodicity of 8 years. This regime was replaced by dynamics more typical of southern latitude hare populations from 1909 to 1970, in which cycles were lost and numbers declined dramatically. Destabilization of the autumn North Atlantic Oscillation (NAO) led to the collapse of similar cycles in the hare population, coincident with the onset of agricultural intensification (a shift from small‐to‐large farms) in the first half of the 20th century. Similar, but more recent regime shifts have been observed in Arctic ecosystems and attributed to anthropogenic climate change. The present study suggests such shifts may have occurred at lower latitudes more than a century ago during the very early 20th century. It seems likely that similar tipping points in the population collapse of other farmland species may have occurred similarly early but went undocumented. As northern systems are increasingly impacted by climate change and probable expansion of agriculture, the interaction of these processes is likely to disrupt the pulsed flow of resources from cyclic populations impacting ecosystem function.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Gimme Shelter: differential utilisation and propagule creation of invasive macrophytes by native caddisfly larvae - Kate Crane; Ross N. Cuthbert; Anthony Ricciardi; Louise Kregting; Neil E. Coughlan; Hugh J. MacIsaac; Neil Reid; Jaimie T. A. Dick (Biological Invasions, 2021)
In aquatic systems, invasive submerged macrophytes considerably alter the structure and functioning of communities, thus potentially compromising ecosystem services. The prolific spread of invasive macrophytes is often aided by vegetative fragment propagation, yet the contributions of various commonly occurring invertebrates to such fragmentation are often unquantified. In the present study, we examine fragmentary spread of invasive macrophytes by a group of shredder-herbivores, larval caddisflies. Through novel application of the comparative functional response (FR; resource use as a function of density) approach to the native case-building species Limnephilus lunatus , we compared utilisation of non-native waterweeds Elodea canadensis and E. nuttallii in mono- and polycultures. Furthermore, we quantified de-cased and cased caddisfly-induced fragment production and length changes among non-native E. canadensis , E. nuttallii , Crassula helmsii and Lagarosiphon major under two different plant orientations: horizontal (floating) versus vertical (upright) growth forms. Larval caddisflies exhibited Type II (hyperbolic) FRs towards both Elodea species, and utilised each plant at similar rates when plants were provided separately. When plant species were presented in combination horizontally, E. canadensis was significantly less utilised compared to E. nuttallii , corroborating observations in the field. De-cased larvae produced new plant fragments for all four aquatic macrophytes, whereas cased larvae fragmented plants significantly less. Elodea nuttalii and C. helmsii were fragmented the most overall. Crassula helmsii was utilised to the greatest extent when plants were horizontally orientated, and Elodea species when vertically orientated. This study identifies and quantifies a mechanism from a novel species group that may contribute to the spread of invasive macrophytes in aquatic systems. Whilst exploititative interactions are thought to impede invasion success, here we demonstrate how resource utilisation by a resident species may exacerbate propagule pressure from an invasive species.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Correction to: Wheat wounding-responsive HD-Zip IV transcription factor GL7 is predominantly expressed in grain and activates genes encoding defensins - Nataliya Kovalchuk; Wei Wu; Natalia Bazanova; Nicolas Reid; Rohan Singh; Neil Shirley; Omid Eini; Alexander A. T. Johnson; Peter Langridge; Maria Hrmova; Sergiy Lopato (Plant Molecular Biology, 2019)

Wheat wounding-responsive HD-Zip IV transcription factor GL7 is predominantly expressed in grain and activates genes encoding defensins - Nataliya Kovalchuk; Wei Wu; Natalia Bazanova; Nicolas Reid; Rohan Singh; Neil Shirley; Omid Eini; Alexander A. T. Johnson; Peter Langridge; Maria Hrmova; Sergiy Lopato (Plant Molecular Biology, 2019)

The use of historical environmental monitoring data to test predictions on cross-scale ecological responses to alterations in river flows - Matthew J. Colloff; Ian C. Overton; Brent L. Henderson; Jane Roberts; Julian R. W. Reid; Roderick L. Oliver; Anthony D. Arthur; Tanya M. Doody; Neil C. Sims; Qifeng Ye; Susan M. Cuddy (Aquatic Ecology, 2018)

Nutrients from salmon parents alter selection pressures on their offspring - Sonya K. Auer; Graeme J. Anderson; Simon McKelvey; Ronald D. Bassar; Darryl McLennan; John D. Armstrong; Keith H. Nislow; Helen K. Downie; Lynn McKelvey; Thomas A.J. Morgan; Karine Salin; Danielle L. Orrell; et al. (Ecology Letters, 2018)
Organisms can modify their surrounding environment, but whether these changes are large enough to feed back and alter their evolutionary trajectories is not well understood, particularly in wild populations. Here we show that nutrient pulses from decomposing Atlantic salmon ( Salmo salar ) parents alter selection pressures on their offspring with important consequences for their phenotypic and genetic diversity. We found a strong survival advantage to larger eggs and faster juvenile metabolic rates in streams lacking carcasses but not in streams containing this parental nutrient input. Differences in selection intensities led to significant phenotypic divergence in these two traits among stream types. Stronger selection in streams with low parental nutrient input also decreased the number of surviving families compared to streams with high parental nutrient levels. Observed effects of parent‐derived nutrients on selection pressures provide experimental evidence for key components of eco‐evolutionary feedbacks in wild populations.

Applying species distribution modelling to a data poor, pelagic fish complex: the ocean sunfishes - Natasha D. Phillips; Neil Reid; Tierney Thys; Chris Harrod; Nicholas L. Payne; Cheryl A. Morgan; Hannah J. White; Siobhán Porter; Jonathan D.R. Houghton (Journal of Biogeography, 2017)
Aim Conservation management of vulnerable species requires detailed knowledge of their spatial and temporal distribution patterns. Within this context, species distribution modelling ( SDM ) can provide insights into the spatial ecology of rarely encountered species and is used here to explore the distribution pattern of ocean sunfishes ( Mola mola and M. ramsayi ). Both species are prone to high levels of bycatch and are classified respectively as Globally Vulnerable and Not Assessed by the IUCN ; although their overall range and drivers of distribution remain poorly defined. Here, we constructed suitable habitat models for Mola spp. on a global scale and considered how these change seasonally to provide a much needed baseline for future management. Location Global. Methods Sighting records collected between 2000 and 2015 were used to build SDM s and provided the first global overview of sunfish seasonal distribution. Post hoc analyses provided a quantitative assessment of seasonal changes in total range extent and latitudinal shifts in suitable habitat. Results Mola is a widely distributed genus; however, sightings exhibited significant spatial clustering most notably in coastal regions. SDM s suggested that Mola presence was strongly dependent on sea surface temperatures with highest probability of presence between 16 and 23°C. The models identified significant variation in seasonal range extent with latitudinal shifts throughout the year; although large areas of suitable year‐round habitat exist globally. Main conclusions We provided the first assessment of Mola distribution on a global scale, with evidence of a wide latitudinal range and significant clustering in localized “hotspots” (notably between 40–50°N). By assessing the results of SDM s alongside evidence from published satellite tagging studies, we suggest that the species within the genus Mola are highly mobile, acting as facultative seasonal migrants. By identifying key suitable habitat alongside potential movement paths, this study provides a baseline that can be used in active conservation management of the genus.

Detection of a novel gammaherpesvirus (genus Rhadinovirus) in wild muntjac deer in Northern Ireland - John McKillen; Kayleigh Hogg; Paula Lagan; Cheryl Ball; Simon Doherty; Neil Reid; Lisa Collins; Jaimie T. A. Dick (Archives of Virology, 2017)

Niche overlap of mountain hare subspecies and the vulnerability of their ranges to invasion by the European hare; the (bad) luck of the Irish - Anthony Caravaggi; Katie Leach; Francesco Santilli; Jukka Rintala; Pekka Helle; Juha Tiainen; Francesco Bisi; Adriano Martinoli; W. Ian Montgomery; Neil Reid (Biological Invasions, 2017)

Erratum to: Range expansion and comparative habitat use of insular, congeneric lagomorphs: invasive European hares Lepus europaeus and endemic Irish hares Lepus timidus hibernicus - Anthony Caravaggi; W. Ian Montgomery; Neil Reid (Biological Invasions, 2016)

Effects of Elodea nuttallii on temperate freshwater plants, microalgae and invertebrates: small differences between invaded and uninvaded areas - Ruth Kelly; Chris Harrod; Christine A. Maggs; Neil Reid (Biological Invasions, 2015)

Lack of genetic structure and evidence for long-distance dispersal in ash (Fraxinus excelsior) populations under threat from an emergent fungal pathogen: implications for restorative planting - Gemma E. Beatty; James A. Brown; Eamon M. Cassidy; Caroline M. V. Finlay; Lorraine McKendrick; W. Ian Montgomery; Neil Reid; David G. Tosh; Jim Provan (Tree Genetics & Genomes, 2015)

Range expansion and comparative habitat use of insular, congeneric lagomorphs: invasive European hares Lepus europaeus and endemic Irish hares Lepus timidus hibernicus - Anthony Caravaggi; W. Ian Montgomery; Neil Reid (Biological Invasions, 2015)

Invasive alien species disrupt spatial and temporal ecology and threaten extinction in an insular, small mammal community - W. Ian Montgomery; Sally S. J. Montgomery; Neil Reid (Biological Invasions, 2015)

Detecting detectability: identifying and correcting bias in binary wildlife surveys demonstrates their potential impact on conservation assessments - Neil Reid; Mathieu G. Lundy; Brian Hayden; Deirdre Lynn; Ferdia Marnell; Robbie A. McDonald; W. Ian Montgomery (European Journal of Wildlife Research, 2013)

Ecological impacts of an invasive predator explained and predicted by comparative functional responses - Jaimie T. A. Dick; Kevin Gallagher; Suncica Avlijas; Hazel C. Clarke; Susan E. Lewis; Sally Leung; Dan Minchin; Joe Caffrey; Mhairi E. Alexander; Cathy Maguire; Chris Harrod; Neil Reid; et al. (Biological Invasions, 2013)

Range expansion in an invasive small mammal: influence of life-history and habitat quality - Thomas A. White; Mathieu G. Lundy; W. Ian Montgomery; Sally Montgomery; Sarah E. Perkins; Colin Lawton; John M. Meehan; Tom J. Hayden; Gerald Heckel; Neil Reid; Jeremy B. Searle (Biological Invasions, 2012)

‘Invasional meltdown’: evidence for unexpected consequences and cumulative impacts of multispecies invasions - W. Ian Montgomery; Mathieu G. Lundy; Neil Reid (Biological Invasions, 2012)

Changes in the prevalence of badger persecution in Northern Ireland - Neil Reid; Gavin J. Wilson; W. Ian Montgomery; Robbie A. McDonald (European Journal of Wildlife Research, 2012)

European hare (Lepus europaeus) invasion ecology: implication for the conservation of the endemic Irish hare (Lepus timidus hibernicus) - Neil Reid (Biological Invasions, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The effect of different HUFA enrichment emulsions on the nutritional value of rotifers (Brachionus plicatilis) fed to larval haddock (Melanogrammus aeglefinus). - John Castell; Tammy Blair; Steven Neil; Kenneth Howes; Sarah Mercer; John Reid; Wilfred Young-Lai; Brandi Gullison; Philippe Dhert; Patrick Sorgeloos (Aquaculture International, 2003)